A method for preparing anode diffusion layer of PEM water electrolysis
By using titanium nanotubes with different pore sizes and precious metal oxide treatments, combined with polymer resin sealing and batch drying technology, the PEM water electrolytic anode diffusion layer has been solved, and an anode diffusion layer with high conductivity, high porosity and mechanical strength has been achieved.
Patent Information
- Application Number
- CN202310024481.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-06
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-01-06
AI Technical Summary
The existing PEM water electrolytic anode diffusion layer has poor conductivity and is easy to oxidize, and has poor water gas management capabilities at high potentials.
Titanium nanotubes with different pore sizes are used to improve conductivity and catalytic capacity through pickling and noble metal oxide treatment, and an anode diffusion layer with high conductivity and high porosity is formed through polymer resin sealing and batch drying.
Good water and gas management and conductivity at high potentials are achieved, the mechanical strength and stability of the anode diffusion layer are improved, and the life of the catalyst is extended.
Abstract
Description
Technical Field
[0001] The invention belongs to the field of PEM water electrolysis, and in particular relates to a method for preparing a PEM water electrolysis anode diffusion layer. Background Art
[0002] As the international community's awareness of clean energy continues to improve, and domestic policies to support hydrogen energy are increasing, the demand for hydrogen will increase. PEM water electrolysis technology can use excess electricity from renewable energy sources such as wind and light to produce hydrogen, while alleviating the pressure on the power grid. PEM water electrolysis has many advantages. In the hydrogen production process, only water is needed as a raw material, and the product hydrogen and oxygen are of high purity, with little mutual penetration. The electrolysis process is efficient, safe, non-toxic and harmless, and the equipment has a compact structure, which can achieve on-site hydrogen production without considering the issue of hydrogen transportation.
[0003] The anode diffusion layer is one of the key technologies in PEM water electrolysis technology. It plays the role of conducting electricity, separating water flow and bubbles, and supporting in the PEM water electrolysis cell. Therefore, the mechanical properties, conductivity, chemical stability, and cost of the anode diffusion layer material are very high. Its cost accounts for a large part of the various components of the PEM stack. Therefore, the research on low-cost, high-chemical stability, and high-conductivity anode diffusion layers is crucial.
[0004] Titanium materials are commonly used in the anode diffusion layer of PEM electrolytic cells, including sintered titanium plates, titanium fiber felts, and titanium meshes. Sintered titanium plates are cheap, with a porosity generally lower than 50% and a thickness generally greater than 0.5 mm, which increases the resistance of the electrolytic cell and does not meet the gas-liquid mass transfer requirements. Titanium fiber felt has a porosity of more than 70% and a minimum thickness of 0.2 mm. Its mechanical properties can meet the needs of the electrolytic cell, but it is relatively expensive. Titanium mesh is cheap, has a high porosity but the pores are too large, and is thicker than 1 mm, which basically cannot meet the mass transfer requirements and has the worst actual performance when used in electrolytic cells.
[0005] Patent CN112647086A discloses a titanium fiber felt anode diffusion layer for a PEM water electrolysis cell and its preparation method and application. The titanium fiber felt is subjected to surface etching treatment, and a precious metal oxide coating suitable for PEM water electrolysis is prepared in a targeted manner. The coating is strengthened according to the properties of PEM water electrolysis to improve the catalytic effect and life of the coating. However, the patent still uses titanium felt as the substrate. Although the surface is coated with a precious metal oxide to improve its catalytic performance, the coating is easy to fall off. At high potential, more gas needs to be discharged through the anode diffusion layer, and the porosity requirement is relatively high to facilitate water vapor transmission and electron transfer.
[0006] Therefore, the development of an anode gas diffusion layer with excellent water vapor management and electrical conductivity is of utmost importance in the development of water electrolysis. Summary of the invention
[0007] In response to the problems of poor conductivity, easy oxidation, and poor water vapor management ability under high potential in the existing PEM water electrolysis anode diffusion layer, a water electrolysis anode diffusion layer with high conductivity, high porosity, and rationally distributed water vapor conduction has been developed. It is very effective in alleviating the problems of poor water vapor management ability and poor performance under high potential in water electrolysis.
[0008] In order to solve the above technical problems, the present invention provides a method for preparing a PEM water electrolysis anode diffusion layer, comprising the following steps:
[0009] Step 1: chopping titanium nanotube fiber materials a and titanium nanotube fiber materials b with two pore sizes to form small-pore titanium nanotubes A and large-pore titanium nanotubes B, respectively;
[0010] Step 2: prepare acid solution;
[0011] Step 3: respectively placing the titanium powder, the small-aperture titanium nanotube A obtained in step 1, and the large-aperture titanium nanotube B into the acid solution obtained in step 2 for pickling; after pickling, ultrasonically cleaning with deionized water, and then drying for standby use;
[0012] Step 4: Add iridium chloride hexahydrate 2 IrCl 6 6H 2 O and ruthenium chloride trihydrate RuCl 3 ·3H 2 O is dissolved in deionized water to prepare a noble metal solution, and the titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B treated in step 3 are respectively immersed in the noble metal solution;
[0013] Step 5: calcining the titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B after the treatment in step 4 with oxygen, so that the noble metal ions are converted into metal oxides, thereby forming titanium powder with metal oxides, small-pore titanium nanotube A, and large-pore titanium nanotube B, respectively;
[0014] Step 6: Weigh a polymer resin and add it to a solvent to obtain a polymer resin solution, and immerse the small-pore titanium nanotube A and the large-pore titanium nanotube B with metal oxide prepared in step 5 in the polymer resin solution respectively, and then take them out and dry them;
[0015] Step 7: Mix the titanium powder with metal oxide after the treatment in step 5, and the small-pore titanium nanotube A and large-pore titanium nanotube B with metal oxide after the treatment in step 6 with a binder, a dispersant, and deionized water, and stir and disperse them to form a viscous mixed slurry;
[0016] Step 8: pour the viscous mixed slurry prepared in step 7 into a closed mold, and perform intermittent drying until the slurry in the mold is formed and a formed slurry with a solvent content of 10-30wt.% is formed, and then taken out for use;
[0017] Step 9: The formed slurry obtained in step 8 is subjected to a pressure treatment, and then subjected to a calcination treatment to obtain an anode diffusion layer.
[0018] Furthermore, in step 1, the pore size of titanium nanotube fiber material a is 20-50 μm, and the pore size of titanium nanotube fiber material b is 50-100 μm; after short cutting, the length of small-pore titanium nanotube A and large-pore titanium nanotube B are both 1-5 mm; in step 3, the particle size of titanium powder is 30-200 μm.
[0019] Furthermore, in step 2, the acid solution is a mixed acid solution of hydrofluoric acid and hydrochloric acid, and the preparation method of the mixed acid solution is: weighing hydrofluoric acid solution and hydrochloric acid solution, adding them to deionized water and stirring and mixing; wherein the specification of the hydrofluoric acid solution is 40wt.%, and the specification of the hydrochloric acid solution is 36.5wt.%; in the mixed acid solution, the mass ratio of hydrofluoric acid solution: hydrochloric acid solution: deionized water is 1:1-3:10-15.
[0020] Furthermore, in step 3, the pickling time is 30-50 minutes, the pickling temperature is 50-70°C; the deionized water ultrasonic cleaning number is 5-8 times; the drying temperature is 60-80°C, and the drying time is 4-6 hours.
[0021] Furthermore, in step 4, the mass concentration of the noble metal solution is 5-15wt.%, and the hexahydrate chloroiridic acid H 2 IrCl 6 6H 2 O and ruthenium chloride trihydrate RuCl 3 ·3H 2 The molar ratio of O is 6:0.5-1; the soaking time is 30-60min.
[0022] Furthermore, in step 5, the temperature of oxygen calcination is 350-450° C., and the calcination time is 1-2 h.
[0023] Furthermore, in step 6, the preparation method of the polymer resin solution is: weigh the polymer resin, add it to an organic solvent, and stir to dissolve; wherein the organic solvent is any one of N-methylpyrrolidone and N,N-diformamide; the polymer resin is any one of soluble polyimide, polycarbonate, polypropylene, and polyethylene; the concentration of the polymer resin solution is 3-6wt.%; the immersion time is 15-30min, and the drying temperature is 60-80°C.
[0024] Furthermore, in step 7, the mass ratio of small-pore titanium nanotube A: large-pore titanium nanotube B: titanium powder: binder: dispersant: deionized water is 1:2:0.8-1.2:0.5-0.7:30-50:30-50; the viscosity of the viscous mixed slurry is 200-400cp, the dispersant is an alcohol solvent, and the binder is a 25wt.% PTFE emulsion.
[0025] Furthermore, in step 8, the drying temperature is 80-100° C., the intermittent drying is drying for 10 minutes, stopping heating for 30 minutes, and the number of intermittent drying is 3-5 times.
[0026] Furthermore, in step 9, an extrusion die is used to pressurize the molding slurry, and the molding pressurization pressure is 0.5-0.8 MPa; the calcination temperature is 350-400°C, and the calcination time is 2-4h; the thickness of the prepared anode diffusion layer is 150-200μm.
[0027] Beneficial effects:
[0028] 1. The present invention selects titanium nanotubes with different pore sizes when preparing the anode diffusion layer. The large-pore titanium nanotubes are used to transmit liquids, and the small-pore titanium nanotubes are used to transmit gases, so that the gas and liquid transmission in the PEM water electrolysis process is highly ordered, and good liquid and gas management functions are achieved. At the same time, titanium powder is added to fill the gaps between the nanotubes to ensure the mechanical strength and stability of the diffusion layer;
[0029] In addition, due to the presence of capillary force, the titanium nanotubes with small pore sizes can accelerate the transmission of gas, thereby preventing the oxygen generated on the anode side from being unable to be discharged in time and covering the active sites of the catalyst, thereby affecting the electrolysis efficiency; and due to the presence of the small-pore nanotubes, the present invention has a good exhaust effect, so the present invention does not need to have a high porosity, that is, the present invention can make the base material more compact without affecting the exhaust, thereby further improving the mechanical strength and stability of the diffusion layer;
[0030] 2. The present invention firstly uses a mixed solution of hydrofluoric acid and hydrochloric acid to pickle titanium nanotubes and titanium powder, so that impurities and oxides on the surface of the titanium material are fully cleaned, and the acid can slightly etch the surface of the titanium material into a structure with a certain roughness. Then, the cleaned titanium nanotubes and titanium powder are immersed in a precious metal solution. The above-mentioned roughness structure increases the specific surface area of the titanium material surface and can improve the metal adhesion rate, so that the surface of the titanium nanotubes and titanium powder is fully attached by precious metal ions. Then, oxygen is introduced for calcination, and at the same time, the precious metal ions are controlled by parameters such as the solution concentration of the metal ions and the soaking time, so that the precious metal ions undergo a solid-phase reaction at high temperature to form an oxide grid structure and attach and embed on the surface of the titanium nanotubes and titanium powder, which not only protects the titanium material from being oxidized during the water electrolysis process, but also improves the conductivity and catalytic ability of the anode diffusion layer;
[0031] The existing preparation method is to form a catalyst coating on the surface of the whole titanium felt by physical or chemical deposition. This structure is similar to the form of a sandwich. Although the catalyst coating has a certain stability, the bonding force between the catalyst coating and the substrate layer is poor, and the catalyst layer often detaches after a certain operating time. Compared with this method, the present invention pre-attaches the catalyst layer on the substrate layer and forms a thin film network structure, so that the catalyst and the substrate material form a whole, and the precious metal oxide is embedded in the titanium material surface by chemical bonding, which is more firm. Therefore, it has the advantage of improving the mechanical strength of the substrate without increasing the thickness, and has higher stability.
[0032] 3. The present invention soaks the precious metalized titanium nanotubes in a resin solution, so that the resin solution enters the nanotube diameter and blocks the two sides of the nanotubes, thereby preventing titanium powder from entering the nanotubes and blocking the nanotubes during the preparation of the anode diffusion layer, thereby affecting the liquid and gas transfer functions of the titanium nanotubes. After that, the present invention performs high-temperature sintering before complete forming, so that the binder (PTFE) is melted and then separated to form a uniform water and gas transmission channel; in addition, during this high-temperature sintering process, the resin material in the titanium nanotubes will be completely sintered and gasified, and the blocked titanium nanotubes will be released to form an anode diffusion layer with channels with different nanopore diameters;
[0033] 4. In the process of forming the anode diffusion layer of the present invention, the preforming is firstly performed by using a mold to form a preformed structure with a low solvent content and not completely dried, and then heating and pressurizing are performed. On the one hand, the not completely dried structure is easy to pressurize to form the required structure without cracks. On the other hand, during the heating and pressurizing process, the remaining solvent is completely volatilized during the hot pressing process, and combined with the pressure effect, the titanium nanotubes and titanium powder are forced to densify, so that the gaps between the titanium materials are further reduced, and no large void defects will appear. Therefore, the prepared anode diffusion layer is relatively dense, thereby forming an anode diffusion layer with high density, high strength and suitable size;
[0034] 5. In the preparation method of the molding slurry of the present invention, it is necessary to form a slurry with a certain viscosity under the action of a binder and a dispersant for the molding process. In this process, in order to make the small-pore titanium nanotubes and the large-pore titanium nanotubes more evenly distributed, the present invention is designed to make the dispersant content in the slurry higher, that is, the viscosity of the slurry is lower. At this time, during the high-temperature calcination process of the viscous mixed slurry, if the high-temperature molding is directly performed in one step, the dispersant region will volatilize unevenly. For example, the concentration of the region where the volatilization is faster is increased and the volume is reduced. Since the slurry has a certain fluidity, the large volume will flow to the small volume. Gradually, the slurry in the region will be over-concentrated, resulting in the base of the region being too thick and the rest of the position being thinner.
[0035] The present invention adopts an intermittent calcination method to solve the above-mentioned problems. By adopting a segmented incomplete heating form, the dispersant in the slurry is continuously volatilized to improve the overall consistency of the slurry. When the dispersant content in the slurry is low or even absent, a base layer is formed through high-temperature calcination under the pressure of the mold. The pore size distribution, thickness and pore distribution of the base layer will be more uniform, so that the water vapor management ability of the anode diffusion layer is stronger and the performance is better. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0037] Embodiment 1:
[0038] 1. Weigh 10 g of titanium nanotube fiber material a with a pore size of 20 μm and 10 g of titanium nanotube fiber material b with a pore size of 50 μm, and perform high-speed short-cut processing to form small-pore titanium nanotube A and large-pore titanium nanotube B with a length of 1 mm, respectively, for use;
[0039] 2. Weigh 20 g of 40 wt.% hydrofluoric acid and 20 g of 36.5 wt.% hydrochloric acid and add them to 200 g of deionized water, stir evenly to obtain a mixed acid solution of hydrofluoric acid and hydrochloric acid;
[0040] 3. The 30 μm titanium powder, the small-aperture titanium nanotube A and the large-aperture titanium nanotube B which have been chopped in step 1 are respectively placed in the mixed acid solution of step 2 for separate pickling. The pickling time is 30 min and the pickling temperature is 70° C. After the pickling, they are ultrasonically cleaned with deionized water for 5 times to wash away the excess acid solution. Then, they are placed in a vacuum oven and the vacuum oven temperature is set to 60° C. The drying time is 6 hours. After the drying is completed, they are ready for use.
[0041] 4. Weigh 9.5 g of iridic acid hexahydrate and 0.393 g of ruthenium chloride trihydrate, add them to 187.967 g of deionized water, stir and dissolve to obtain a precious metal solution with a mass concentration of 5 wt.%, and soak the titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B after the treatment in step 3 in the precious metal solution for 60 min respectively for standby use;
[0042] 5. The titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B treated in step 4 are subjected to high-temperature calcination in oxygen, the high-temperature calcination temperature is 350° C., and the calcination time is 2 h to form titanium powder with metal oxide, small-pore titanium nanotube A, and large-pore titanium nanotube B;
[0043] 6. Weigh 3 g of polycarbonate and add it to 97 g of N-methylpyrrolidone to obtain a polymer resin solution with a mass concentration of 3 wt.%; soak the small-pore titanium nanotubes A and large-pore titanium nanotubes B with metal oxides prepared in step 5 in the polymer resin solution for 15 minutes, then take them out and dry them at 60°C;
[0044] 7. Weigh 1.6 g of the titanium powder with metal oxide treated in step 5, 2 g of the small-pore titanium nanotube A with metal oxide treated in step 6, and 4 g of the large-pore titanium nanotube B with metal oxide, and weigh 4 g of 25 wt.% binder (PTFE), 60 g of ethanol, and 60 g of deionized water, and mix and disperse them together by stirring to form a mixed slurry with a viscosity of 400 cp;
[0045] 8. Pour the mixed slurry prepared in step 7 into a closed mold, and place it in a vacuum oven for intermittent high-temperature treatment, wherein the oven temperature is 80° C. During intermittent drying, dry for 10 minutes, stop heating for 30 minutes, and repeat for 3 times until the slurry in the mold is formed, wherein the solvent content in the formed slurry is 10 wt.%, and then take it out for use;
[0046] 9. The formed slurry obtained in step 8 is pressurized to a pressure of 0.5 MPa, and then placed in a vacuum oven again for high-temperature calcination, wherein the high-temperature calcination temperature is 350°C and the calcination time is 4 hours. After the calcination is completed, the mold is removed to obtain an anode diffusion layer with a thickness of 200 μm.
[0047] Embodiment 2:
[0048] 1. Weigh 10 g of titanium nanotube fiber material a with a pore size of 50 μm and 10 g of titanium nanotube fiber material b with a pore size of 100 μm, and perform high-speed short-cut processing to form small-pore titanium nanotube A and large-pore titanium nanotube B with a length of 5 mm, respectively, for standby use;
[0049] 2. Weigh 10 g of 40 wt.% hydrofluoric acid and 30 g of 36.5 wt.% hydrochloric acid and add them to 150 g of deionized water, stir evenly to obtain a mixed acid solution of hydrofluoric acid and hydrochloric acid;
[0050] 3. Put the 200 μm titanium powder, the small-aperture titanium nanotube A and the large-aperture titanium nanotube B that have been chopped in step 1 into the mixed acid solution of step 2 for pickling separately. The pickling time is 50 min and the pickling temperature is 50° C. After the pickling, use deionized water to ultrasonically clean 8 times to wash away the excess acid solution, and then put them into a vacuum oven. Set the vacuum oven temperature to 80° C. and dry for 4 hours. After drying, set aside;
[0051] 4. Weigh 9.5 g of iridic acid hexahydrate and 0.786 g of ruthenium chloride trihydrate, add them to 58.287 g of deionized water, stir and dissolve to obtain a precious metal solution with a mass concentration of 15 wt.%, and soak the titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B after the treatment in step 3 in the precious metal solution for 30 min respectively, and set aside;
[0052] 5. The titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B treated in step 4 are subjected to high-temperature calcination in oxygen, the high-temperature calcination temperature is 450° C., and the calcination time is 1 h to form titanium powder with metal oxide, small-pore titanium nanotube A, and large-pore titanium nanotube B;
[0053] 6. Weigh 12g of polypropylene and add it to 188g of N,N-diformamide to obtain a polymer resin solution with a mass concentration of 6wt.%; soak the small-pore titanium nanotubes A and large-pore titanium nanotubes B with metal oxides prepared in step 5 in the polymer resin solution for 30min respectively, and then take them out and dry them at 80°C;
[0054] 7. Weigh 2.4 g of the titanium powder with metal oxide treated in step 5, 2 g of the small-pore titanium nanotube A with metal oxide treated in step 6, and 4 g of the large-pore titanium nanotube B with metal oxide, and weigh 5.6 g of 25 wt.% binder (PTFE), 100 g of ethanol, and 100 g of deionized water, mix and disperse them together by stirring to form a mixed slurry with a viscosity of 200 cp;
[0055] 8. Pour the mixed slurry prepared in step 7 into a closed mold, and place it in a vacuum oven for intermittent high-temperature treatment, wherein the oven temperature is 100° C. During intermittent drying, dry for 10 minutes, stop heating for 30 minutes, and repeat 5 times until the slurry in the mold is formed, wherein the solvent content in the formed slurry is 30 wt.%, and then take it out for use;
[0056] 9. The formed slurry obtained in step 8 is pressurized to a pressure of 0.8 MPa, and then placed in a vacuum oven again for high-temperature calcination, wherein the high-temperature calcination temperature is 400°C and the calcination time is 2 hours. After the calcination is completed, the mold is removed to obtain an anode diffusion layer with a thickness of 150 μm.
[0057] Embodiment 3:
[0058] 1. Weigh 10 g of titanium nanotube fiber material a with a pore size of 40 μm and 10 g of titanium nanotube fiber material b with a pore size of 70 μm, and perform high-speed short-cut processing to form small-pore titanium nanotube A and large-pore titanium nanotube B with a length of 3 mm, respectively, for standby use;
[0059] 2. Weigh 20 g of 40 wt.% hydrofluoric acid and 40 g of 36.5 wt.% hydrochloric acid and add them to 240 g of deionized water, stir evenly to obtain a mixed acid solution of hydrofluoric acid and hydrochloric acid;
[0060] 3. Put the 100 μm titanium powder, the small-aperture titanium nanotube A and the large-aperture titanium nanotube B that have been chopped in step 1 into the mixed acid solution of step 2 for pickling separately. The pickling time is 40 minutes and the pickling temperature is 60°C. After the pickling, use deionized water to ultrasonically clean 7 times to wash away the excess acid solution, and then put them into a vacuum oven. Set the vacuum oven temperature to 70°C and dry for 5 hours. After drying, set them aside;
[0061] 4. Weigh 9.5 g of iridic acid hexahydrate and 0.55 g of ruthenium chloride trihydrate, add them to 90.45 g of deionized water, stir and dissolve to obtain a noble metal solution with a mass concentration of 10 wt.%, and soak the titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B after the treatment in step 3 in the noble metal solution for 40 min respectively for standby use;
[0062] 5. The titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B treated in step 4 are respectively subjected to high-temperature calcination with oxygen, the high-temperature calcination temperature is 400° C., and the calcination time is 1.5 h to form titanium powder with metal oxide, small-pore titanium nanotube A, and large-pore titanium nanotube B;
[0063] 6. Weigh 5g of polyethylene and add it to 95g of N-methylpyrrolidone to obtain a polymer resin solution with a mass concentration of 5wt.%; soak the small-pore titanium nanotubes A and large-pore titanium nanotubes B with metal oxide prepared in step 5 in the polymer resin solution for 20min respectively, then take them out and dry them at 70°C;
[0064] 7. Weigh 2 g of the titanium powder with metal oxide treated in step 5, 2 g of the small-pore titanium nanotube A with metal oxide treated in step 6, and 4 g of the large-pore titanium nanotube B with metal oxide, and weigh 4.8 g of 25 wt.% binder (PTFE), 80 g of ethanol, and 80 g of deionized water, mix and disperse them together by stirring to form a mixed slurry with a viscosity of 300 cp;
[0065] 8. Pour the mixed slurry prepared in step 7 into a closed mold, and place it in a vacuum oven for intermittent high-temperature treatment, wherein the oven temperature is 90° C. During intermittent drying, dry for 10 minutes, stop heating for 30 minutes, and repeat 4 times until the slurry in the mold is formed, wherein the solvent content in the formed slurry is 20 wt.%, and then take it out for use;
[0066] 9. The formed slurry obtained in step 8 is pressurized to a pressure of 0.6 MPa, and then placed in a vacuum oven again for high-temperature calcination treatment, wherein the high-temperature calcination temperature is 380°C and the calcination time is 3 hours. After the calcination is completed, the mold is removed to obtain an anode diffusion layer with a thickness of 180 μm.
[0067] Comparative Example 1: (All small-aperture titanium nanotube fiber materials are selected)
[0068] 1. Weigh 10 g of titanium nanotube fiber material a with a pore size of 20 μm and perform high-speed short-cutting to form small-pore titanium nanotubes A with a length of 1 mm for later use;
[0069] 2. Weigh 20 g of 40 wt.% hydrofluoric acid and 20 g of 36.5 wt.% hydrochloric acid and add them to 200 g of deionized water, stir evenly to obtain a mixed acid solution of hydrofluoric acid and hydrochloric acid;
[0070] 3. The 30 μm titanium powder and the small-aperture titanium nanotubes A that have been chopped in step 1 are placed in the mixed acid solution of step 2 for pickling separately. The pickling time is 30 min and the pickling temperature is 70° C. After the pickling, they are ultrasonically cleaned with deionized water for 5 times to wash away the excess acid solution. Then, they are placed in a vacuum oven and the vacuum oven temperature is set to 60° C. The drying time is 6 hours. After the drying is completed, they are ready for use.
[0071] 4. Weigh 9.5 g of iridic acid hexahydrate and 0.393 g of ruthenium chloride trihydrate, add them to 187.967 g of deionized water, stir and dissolve to obtain a precious metal solution with a mass concentration of 5 wt.%, and soak the titanium powder and small-pore titanium nanotube A after the treatment in step 3 in the precious metal solution for 60 min respectively for standby use;
[0072] 5. The titanium powder and small-pore titanium nanotube A treated in step 4 are respectively subjected to high-temperature calcination with oxygen, the high-temperature calcination temperature is 350° C., and the calcination time is 2 h to form titanium powder and small-pore titanium nanotube A with metal oxide;
[0073] 6. Weigh 3 g of polycarbonate and add it to 97 g of N-methylpyrrolidone to obtain a polymer resin solution with a mass concentration of 3 wt.%; soak the small-pore titanium nanotubes A with metal oxide prepared in step 5 in the polymer resin solution for 15 minutes, then take it out and dry it at 60°C;
[0074] 7. Weigh 1.6 g of the titanium powder with metal oxide treated in step 5, weigh 2 g of the small-pore titanium nanotube A with metal oxide treated in step 6, and weigh 4 g of 25 wt.% binder (PTFE), 60 g of ethanol, and 60 g of deionized water, mix and disperse them together by stirring to form a mixed slurry with a viscosity of 350 cp;
[0075] 8. Pour the mixed slurry prepared in step 7 into a closed mold, and place it in a vacuum oven for intermittent high-temperature treatment, wherein the oven temperature is 80° C. During intermittent drying, dry for 10 minutes, stop heating for 30 minutes, and repeat for 3 times until the slurry in the mold is formed, wherein the solvent content in the formed slurry is 10 wt.%, and then take it out for use;
[0076] 9. The formed slurry obtained in step 8 is pressurized to a pressure of 0.5 MPa, and then placed in a vacuum oven again for high-temperature calcination, wherein the high-temperature calcination temperature is 350°C and the calcination time is 4 hours. After the calcination is completed, the mold is removed to obtain an anode diffusion layer with a thickness of 160 μm.
[0077] Comparative Example 2: (All choose large-aperture titanium nanotube fiber materials)
[0078] 1. Weigh 10 g of titanium nanotube fiber material B with a pore size of 50 μm, perform high-speed short-cut processing to form large-pore titanium nanotubes B with a length of 1 mm, and set aside;
[0079] 2. Weigh 20 g of 40 wt.% hydrofluoric acid and 20 g of 36.5 wt.% hydrochloric acid and add them to 200 g of deionized water, stir evenly to obtain a mixed acid solution of hydrofluoric acid and hydrochloric acid;
[0080] 3. The 30 μm titanium powder and the large-aperture titanium nanotubes B that were chopped in step 1 were respectively placed in the mixed acid solution of step 2 for pickling separately. The pickling time was 30 min and the pickling temperature was 70° C. After the pickling, they were ultrasonically cleaned with deionized water for 5 times to wash away the excess acid solution. Then, they were placed in a vacuum oven and the vacuum oven temperature was set to 60° C. The drying time was 6 hours. After the drying was completed, they were set aside for use.
[0081] 4. Weigh 9.5 g of iridic acid hexahydrate and 0.393 g of ruthenium chloride trihydrate, add them to 187.967 g of deionized water, stir and dissolve to obtain a precious metal solution with a mass concentration of 5 wt.%, and soak the titanium powder and large-pore titanium nanotubes B after the treatment in step 3 in the precious metal solution for 60 min respectively for later use;
[0082] 5. The titanium powder and the large-pore titanium nanotubes B treated in step 4 are respectively subjected to high-temperature calcination with oxygen, the high-temperature calcination temperature is 350° C., and the calcination time is 2 h to form titanium powder and large-pore titanium nanotubes B with metal oxides;
[0083] 6. Weigh 3 g of polycarbonate and add it to 97 g of N-methylpyrrolidone to obtain a polymer resin solution with a mass concentration of 3 wt.%; soak the macroporous titanium nanotubes B with metal oxide prepared in step 5 in the polymer resin solution for 15 min, then take it out and dry it at 60°C;
[0084] 7. Weigh 1.6 g of the titanium powder with metal oxide treated in step 5, weigh 4 g of the large-pore titanium nanotube B with metal oxide treated in step 6, and weigh 4 g of a 25 wt.% binder (PTFE), 60 g of ethanol, and 60 g of deionized water, and mix and disperse them together to form a mixed slurry with a viscosity of 320 cp;
[0085] 8. Pour the mixed slurry prepared in step 7 into a closed mold, and place it in a vacuum oven for intermittent high-temperature treatment, wherein the oven temperature is 80° C. During intermittent drying, dry for 10 minutes, stop heating for 30 minutes, and repeat for 3 times until the slurry in the mold is formed, wherein the solvent content in the formed slurry is 10 wt.%, and then take it out for use;
[0086] 9. The formed slurry obtained in step 8 is pressurized to a pressure of 0.5 MPa, and then placed in a vacuum oven again for high-temperature calcination, wherein the high-temperature calcination temperature is 350°C and the calcination time is 4 hours. After the calcination is completed, the mold is removed to obtain an anode diffusion layer with a thickness of 180 μm.
[0087] Comparative Example 3: (The pores of titanium nanotubes are not blocked by polymer resin)
[0088] 1. Weigh 10 g of titanium nanotube fiber material a with a pore size of 20 μm and 10 g of titanium nanotube fiber material b with a pore size of 50 μm, and perform high-speed short-cut processing to form small-pore titanium nanotube A and large-pore titanium nanotube B with a length of 1 mm, respectively, for use;
[0089] 2. Weigh 20 g of 40 wt.% hydrofluoric acid and 20 g of 36.5 wt.% hydrochloric acid and add them to 200 g of deionized water, stir evenly to obtain a mixed acid solution of hydrofluoric acid and hydrochloric acid;
[0090] 3. The 30 μm titanium powder, the small-aperture titanium nanotube A and the large-aperture titanium nanotube B which have been chopped in step 1 are respectively placed in the mixed acid solution of step 2 for separate pickling. The pickling time is 30 min and the pickling temperature is 70° C. After the pickling, they are ultrasonically cleaned with deionized water for 5 times to wash away the excess acid solution. Then, they are placed in a vacuum oven and the vacuum oven temperature is set to 60° C. The drying time is 6 hours. After the drying is completed, they are ready for use.
[0091] 4. Weigh 9.5 g of iridic acid hexahydrate and 0.393 g of ruthenium chloride trihydrate, add them to 187.967 g of deionized water, stir and dissolve to obtain a precious metal solution with a mass concentration of 5 wt.%, and soak the titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B after the treatment in step 3 in the precious metal solution for 60 min respectively for standby use;
[0092] 5. The titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B treated in step 4 are subjected to high-temperature calcination in oxygen, the high-temperature calcination temperature is 350° C., and the calcination time is 2 h to form titanium powder with metal oxide, small-pore titanium nanotube A, and large-pore titanium nanotube B;
[0093] 6. Weigh 1.6 g of the titanium powder with metal oxide treated in step 5, 2 g of the small-pore titanium nanotube A with metal oxide, 4 g of the large-pore titanium nanotube B with metal oxide, and weigh 4 g of a 25 wt.% binder (PTFE), 60 g of ethanol, and 60 g of deionized water, mix and disperse them together by stirring to form a mixed slurry with a viscosity of 400 cp;
[0094] 7. Pour the mixed slurry prepared in step 6 into a closed mold, and place it in a vacuum oven for intermittent high-temperature treatment, wherein the oven temperature is 80° C. During intermittent drying, dry for 10 minutes, stop heating for 30 minutes, and repeat 3 times until the slurry in the mold is formed, wherein the solvent content in the formed slurry is 10 wt.%, and then take it out for use;
[0095] 8. The formed slurry obtained in step 7 is pressurized to a pressure of 0.5 MPa, and then placed in a vacuum oven again for high-temperature calcination, wherein the high-temperature calcination temperature is 350°C and the calcination time is 4 hours. After the calcination is completed, the mold is removed to obtain an anode diffusion layer with a thickness of 200 μm.
[0096] Comparative Example 4: (The molded slurry was not calcined in step 9)
[0097] 1. Weigh 10 g of titanium nanotube fiber material a with a pore size of 20 μm and 10 g of titanium nanotube fiber material b with a pore size of 50 μm, and perform high-speed short-cut processing to form small-pore titanium nanotube A and large-pore titanium nanotube B with a length of 1 mm, respectively, for use;
[0098] 2. Weigh 20 g of 40 wt.% hydrofluoric acid and 20 g of 36.5 wt.% hydrochloric acid and add them to 200 g of deionized water, stir evenly to obtain a mixed acid solution of hydrofluoric acid and hydrochloric acid;
[0099] 3. The 30 μm titanium powder, the small-aperture titanium nanotube A and the large-aperture titanium nanotube B which have been chopped in step 1 are respectively placed in the mixed acid solution of step 2 for separate pickling. The pickling time is 30 min and the pickling temperature is 70° C. After the pickling, they are ultrasonically cleaned with deionized water for 5 times to wash away the excess acid solution. Then, they are placed in a vacuum oven and the vacuum oven temperature is set to 60° C. The drying time is 6 hours. After the drying is completed, they are ready for use.
[0100] 4. Weigh 9.5 g of iridic acid hexahydrate and 0.393 g of ruthenium chloride trihydrate, add them to 187.967 g of deionized water, stir and dissolve to obtain a precious metal solution with a mass concentration of 5 wt.%, and soak the titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B after the treatment in step 3 in the precious metal solution for 60 min respectively for standby use;
[0101] 5. The titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B treated in step 4 are subjected to high-temperature calcination in oxygen, the high-temperature calcination temperature is 350° C., and the calcination time is 2 h to form titanium powder with metal oxide, small-pore titanium nanotube A, and large-pore titanium nanotube B;
[0102] 6. Weigh 3 g of polycarbonate and add it to 97 g of N-methylpyrrolidone to obtain a polymer resin solution with a mass concentration of 3 wt.%; soak the small-pore titanium nanotubes A and large-pore titanium nanotubes B with metal oxides prepared in step 5 in the polymer resin solution for 15 minutes, then take them out and dry them at 60°C;
[0103] 7. Weigh 1.6 g of the titanium powder with metal oxide treated in step 5, 2 g of the small-pore titanium nanotube A with metal oxide treated in step 6, and 4 g of the large-pore titanium nanotube B with metal oxide, and weigh 4 g of 25 wt.% binder (PTFE), 60 g of ethanol, and 60 g of deionized water, and mix and disperse them together by stirring to form a mixed slurry with a viscosity of 400 cp;
[0104] 8. Pour the mixed slurry prepared in step 7 into a closed mold, and place it in a vacuum oven for intermittent high-temperature treatment, wherein the oven temperature is 80° C. During intermittent drying, dry for 10 minutes, stop heating for 30 minutes, and repeat for 3 times until the slurry in the mold is formed, wherein the solvent content in the formed slurry is 10 wt.%, and then take it out for use;
[0105] 9. The formed slurry obtained in step 8 is pressurized to a pressure of 0.5 MPa, and then placed in a vacuum oven for drying again. After drying, the mold is removed to obtain an anode diffusion layer with a thickness of 230 μm.
[0106] It should be noted that the titanium nanotube fiber material a and the titanium nanotube fiber material b used in the present application are both existing technologies and are provided by Ningbo Olike Precision Pipe Manufacturing Co., Ltd.
[0107] The electrochemical performance results of the membrane electrodes prepared using the anode diffusion layers in the examples and comparative examples are shown in Table 1.
[0108] The test conditions are as follows: the anode diffusion layers prepared in the examples and comparative examples are assembled into 5 cm 2 Steady-state polarization curve of electrolytic cell, anode catalyst is 2mg / cm 2 Ir black, cathode catalyst is 0.5mgPt / cm 2 70% Pt / C, the proton exchange membrane is Nafion115 membrane, and the test temperature is 80°C.
[0109] Table 1 Membrane electrode electrolysis current density table
[0110] <![CDATA[Current density mA / cm 2 @ 1.8V]]> <![CDATA[Current density mA / cm 2 @ 2.0V]]> Example 1 1842 2053 Example 2 1876 2098 Example 3 1821 2013 Comparative Example 1 1610 1790 Comparative Example 2 1654 1821 Comparative Example 3 1234 1543 Comparative Example 4 1124 1432
[0111] As shown in Table 1, the anode diffusion layer for water electrolysis prepared by the present invention has excellent electrochemical activity of the membrane electrode. At an electrolysis voltage of 2.0 V, its current density is 2000 mA / cm 2 above.
[0112] In the comparative examples, in comparative example 1, titanium nanofiber tubes with small pore sizes are used in the preparation of the anode diffusion layer. Due to the small pore size of the prepared anode diffusion layer, oxygen is filled in the pore size of the titanium nanotubes, resulting in obstruction of the mass transfer of deionized water, affecting its electrocatalytic performance; in comparative example 2, titanium nanofiber tubes with large pore sizes are selected, and deionized water fills the tube diameter, resulting in obstruction of the transmission of oxygen generated at the anode, causing pressure at the anode, and then oxygen passes through the proton exchange membrane into the cathode, affecting the purity of the cathode hydrogen; in comparative example 3, no comparison is made between the two. In the comparative example 4, after the anode diffusion layer is formed, the anode diffusion layer is not subjected to high-temperature calcination, so the polymer resin blocked in the titanium nanotubes cannot be gasified by high-temperature calcination. In addition, the polymer resin on the surface of the titanium material still exists, resulting in poor conductivity, low porosity, large mass transfer resistance and poor electrochemical performance of the prepared anode diffusion layer.
[0113] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.
Claims
1. A method for preparing a PEM water electrolysis anode diffusion layer, characterized in that: The following steps are involved: Step 1: chopping titanium nanotube fiber materials a and titanium nanotube fiber materials b with two pore sizes to form small-pore titanium nanotubes A and large-pore titanium nanotubes B, respectively; Step 2: prepare acid solution; Step 3: respectively placing the titanium powder, the small-aperture titanium nanotube A obtained in step 1, and the large-aperture titanium nanotube B into the acid solution obtained in step 2 for pickling; after pickling, ultrasonically cleaning with deionized water, and then drying for standby use; Step 4: dissolving iridic acid hexahydrate H2IrCl6·6H2O and ruthenium chloride trihydrate RuCl3·3H2O in deionized water to prepare a noble metal solution, and immersing the titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B treated in step 3 into the noble metal solution respectively; Step 5: calcining the titanium powder, small-pore titanium nanotube A, and large-pore titanium nanotube B after the treatment in step 4 with oxygen, so that the noble metal ions are converted into metal oxides, thereby forming titanium powder with metal oxides, small-pore titanium nanotube A, and large-pore titanium nanotube B, respectively; Step 6: Weigh a polymer resin and add it to a solvent to obtain a polymer resin solution, and immerse the small-pore titanium nanotube A and the large-pore titanium nanotube B with metal oxide prepared in step 5 in the polymer resin solution respectively, and then take them out and dry them; Step 7: Mix the titanium powder with metal oxide after the treatment in step 5, and the small-pore titanium nanotube A and large-pore titanium nanotube B with metal oxide after the treatment in step 6 with a binder, a dispersant, and deionized water, and stir and disperse them to form a viscous mixed slurry; Step 8: pour the viscous mixed slurry prepared in step 7 into a closed mold, perform intermittent drying until the slurry in the mold is formed and a formed slurry with a solvent content of 10-30wt.% is formed, and then take it out for use; Step 9: subjecting the formed slurry obtained in step 8 to a pressurization treatment, and then subjecting the pressurized slurry to a calcination treatment to obtain an anode diffusion layer; In step 1, the pore size of titanium nanotube fiber material a is 20-50 μm, and the pore size of titanium nanotube fiber material b is 50-100 μm; after short cutting, the length of small-pore titanium nanotube A and large-pore titanium nanotube B are both 1-5 mm; in step 3, the particle size of titanium powder is 30-200 μm.
2. The method for preparing the PEM water electrolysis anode diffusion layer according to claim 1, characterized in that: In step 2, the acid solution is a mixed acid solution of hydrofluoric acid and hydrochloric acid, and the preparation method of the mixed acid solution is: weigh hydrofluoric acid solution and hydrochloric acid solution, add them into deionized water and stir to mix; wherein the specification of the hydrofluoric acid solution is 40wt.%, and the specification of the hydrochloric acid solution is 36.5wt.%; in the mixed acid solution, the mass ratio of hydrofluoric acid solution: hydrochloric acid solution: deionized water is 1:1-3:10-15.
3. The method for preparing the PEM water electrolysis anode diffusion layer according to claim 1, characterized in that: In step 3, the pickling time is 30-50 minutes, the pickling temperature is 50-70°C; the deionized water ultrasonic cleaning times are 5-8 times; the drying temperature is 60-80°C, and the drying time is 4-6 hours.
4. The method for preparing a PEM water electrolysis anode diffusion layer according to claim 1, characterized in that: In step 4, the mass concentration of the precious metal solution is 5-15wt.%, the molar ratio of hexahydrate iridium chloride H2IrCl6·6H2O and trihydrate ruthenium chloride RuCl3·3H2O is 6:0.5-1; and the immersion time is 30-60min.
5. The method for preparing a PEM water electrolysis anode diffusion layer according to claim 1, characterized in that: In step 5, the temperature of oxygen calcination is 350-450° C., and the calcination time is 1-2 hours.
6. The method for preparing a PEM water electrolysis anode diffusion layer according to claim 1, characterized in that: In step 6, the preparation method of the polymer resin solution is: weigh the polymer resin, add it to an organic solvent, and stir to dissolve; wherein the organic solvent is any one of N-methylpyrrolidone and N,N-diformamide; the polymer resin is any one of soluble polyimide, polycarbonate, polypropylene, and polyethylene; the concentration of the polymer resin solution is 3-6wt.%; the soaking time is 15-30min, and the drying temperature is 60-80°C.
7. The method for preparing a PEM water electrolysis anode diffusion layer according to claim 1, characterized in that: In step 7, the mass ratio of small-pore titanium nanotube A: large-pore titanium nanotube B: titanium powder: binder: dispersant: deionized water is 1:2:0.8-1.2:0.5-0.7:30-50:30-50; the viscosity of the viscous mixed slurry is 200-400cp, the dispersant is an alcohol solvent, and the binder is 25wt.% PTFE emulsion.
8. The method for preparing a PEM water electrolysis anode diffusion layer according to claim 1, characterized in that: In step 8, the drying temperature is 80-100° C., the intermittent drying is drying for 10 minutes, stopping heating for 30 minutes, and the number of intermittent times is 3-5 times.
9. The method for preparing a PEM water electrolysis anode diffusion layer according to claim 1, characterized in that: In step 9, an extrusion die is used to pressurize the molding slurry, and the molding pressurization pressure is 0.5-0.8 MPa; the calcination temperature is 350-400° C., and the calcination time is 2-4 hours; the thickness of the prepared anode diffusion layer is 150-200 μm.
Citation Information
Patent Citations
Ordered film electrode used for solid polymer water electrolyser and preparing method of ordered film electrode
CN108677209A
Titanium fiber felt anode diffusion layer for PEM water electrolysis tank as well as preparation method and application thereof
CN112647086A